Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

? asked in Science & MathematicsMathematics · 5 years ago

HELP ME WITH THIS MATH EQUATION THNX!?

3x - 2y + z = 12

X + 3y + z = -4

2x + 2y - 4z = 6

4 Answers

Relevance
  • 5 years ago
    Favorite Answer

    (1) : 3x - 2y + z = 12

    (2) : x + 3y + z = - 4

    (3) : 2x + 2y - 4z = 6

    You calculate (1) - (2) and you can get the equation (4)

    (4) : (3x - 2y + z) - (x + 3y + z) = 12 - (- 4)

    (4) : 3x - 2y + z - x - 3y - z = 12 + 4

    (4) : 2x - 5y = 16

    (4) : 2x = 5y + 16

    (4) : x = (5y + 16)/2

    You calculate [4 * (1)] + (3)

    4.(3x - 2y + z) + (2x + 2y - 4z) = (4 * 12) + 6

    12x - 8y + 4z + 2x + 2y - 4z = 48 + 6

    14x - 6y = 54 → recall (4): x = (5y + 16)/2

    [14.(5y + 16)/2] - 6y = 54

    7.(5y + 16) - 6y = 54

    35y + 112 - 6y = 54

    29y = - 58

    → y = - 2

    Recall (4): x = (5y + 16)/2

    x = (- 10 + 16)/2

    → x = 3

    Recall (2): x + 3y + z = - 4

    z = - 4 - x - 3y

    z = - 4 - 3 + 6

    → z = - 1

  • Como
    Lv 7
    5 years ago

    Add 1 and 3

    5x - 3z = 18

    2x + 6y + 2z = - 8

    -6x - 6y + 12z = - 18____ADD

    -4x + 14z = - 26

    5x - 3z = 18

    -4x + 14z = - 26

    20x - 12z = 72

    -20x + 70z = - 130_____ADD

    58z = - 58

    z = - 1

    5x = 15

    x = 3

    3 + 3y - 1 = - 4

    3y = - 6

    y = - 2

    x = 3 , y = - 2 , z = - 1

  • kiko
    Lv 5
    5 years ago

    3x - 2y + z = 12 .....................(1)

    X + 3y + z = -4 ...................(2)

    2x + 2y - 4z = 6...............(3)

    Eliminate any one say x .

    This is done by multiplying eqn 2 by 2 and subtract eqn 3

    6y+2z-2y+4z= -8-6

    4y+6z=-14................................(4)

    Similarly subtract 3 times eqn (2) by (1)

    -2y+z-9y-3z=12+12

    -11y-2z=24.........................(5)

    Solve eqn 4 and 5, multiply 4 by 11 and 5 by 4 and add

    44y+66z-44y-8z=-154+96

    66z-8z=-154+96

    58z= -58

    Z=-1

    -11y-2(-1)=24

    -11y=22

    Y=-2

    Eqn 1

    3x+4-1=12

    X=3

    X=3, y=-1, z=-1

  • Anonymous
    5 years ago

    Manipulate first expression to equal z

    substitute in the second and third expressions to eliminate z

    solve as simultaneous equations in usual way.

Still have questions? Get your answers by asking now.